Attributes of effective EFL teachers in Vietnamese context as perceived by students and teachers - Quan, Nguyen Hai (Indonesian Journal of Applied Linguistics, 2022)
Identifying characteristics of effective teachers has always been a topic of paramount importance. Accordingly, an extensive volume of theoretical endeavours and empirical research has been devoted to the investigation of typical attributes that effective teachers possess in diverse contexts. Yet, current understanding of the issue in Vietnamese setting remains limited. Given that perceptions about effective teachers’ qualities have been typically found to be highly context-bounded, gaining an insight into these attributes in this under-researched context is expected to provide a solid foundation for further attempts to improve the quality of teaching and learning. The present study responds to this pressing need by exploring the perceptions held by 200 learners and 22 teachers in a language school in Vietnam, employing questionnaires for collecting both quantitative and qualitative data. A theoretical framework adapted from Shulman’s (1986, 1987) model of teachers’ knowledge base was employed. Findings from the study revealed both convergence and mismatches in the perceptions held by the teacher and learner groups. As a whole, teachers, and learners convergently prioritised teachers’ subject matter content knowledge as most important, compared to pedagogical content knowledge and teachers’ identity and interactions with learners. Both groups also voted teachers’ ability to provide clear instructions and explanations as the most important pedagogical feature of effective teachers and uniformly downplayed the role of sociocultural knowledge and the ability to effectively use technology. More in-depth analyses, however, showed that teachers placed more importance over the pedagogical aspects of subject matter knowledge, language proficiency, and teaching methodology, whereas learners more appreciated the psychological and motivational aspects. In particular, the teacher participants highly valued the teachers’ ability of classroom management, material adaptation, and facilitating students’ engagement in learning activities. In contrast, qualities most desired by learners included a positive attitude towards the teaching career and teachers’ willingness to care, understand learners’ problems, encourage, and treat all students on a fair basis.